THE INFLUENCE OF GROWTH OPPORTUNITY TOWARDS HEDGING DECISIONS WITH EARNINGS QUALITY AS A MODERATOR - Melati Putri; Thomson Sitompul (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This research is conducted to analyze the influence of Growth Opportunity towards Hedging Decisions with Earnings Quality as the moderating variable in financial sector companies listed in the Indonesia Stock Exchange from 2019 to 2023, as the trend in hedging activities in Indonesia showed a contrasting belief to the Prospect Theory, in which the Indonesian companies hedged more when they might not be doing well in general during times of crisis. The independent variable used in this study is Growth Opportunity alongside 4 control variables. The dependent variable is Hedging Decisions and the moderator variable is Earnings Quality. The research used secondary data from financial sector companies listed in the IDX from 2019 to 2023 and the data source are S&P Capital IQ and Pro. By using the purposive sampling, 90 companies were eligible. The method Logistic Regression analysis is used and processed through SPSS version 25. The outcomes of the research indicate that both Growth Opportunity and Earnings-Quality-moderated Growth Opportunity have insignificant effect towards Hedging Decisions, implying that neither Growth Opportunity nor Earnings-Quality-moderated Growth Opportunity is a consideration for the accounting and management team of the Indonesian financial companies in deciding to carry out hedging activities during 2019-2023.